2009
DOI: 10.1111/j.1365-2036.2008.03883.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: gastro‐oesophageal reflux disease and psychological comorbidity

Abstract: SUMMARY BackgroundA growing number of studies have shown the impact of psychological comorbidities on gastro-oesophageal reflux disease (GERD) patients' symptom reports and healthcare-seeking behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 50 publications
3
32
0
2
Order By: Relevance
“…To improve the overall gastrointestinal symptoms and psychological well-being must also be taken into consideration. Treatment with PPI did not improve gastrointestinal symptoms, which further underlines the conclusion that PPI has no place in the treatment of IBS [25,26]. Irritable bowel syndrome and other functional bowel syndromes are mainly affecting younger persons [23,25], whereas our patients with MC are older.…”
Section: Patients With Irritable Bowel Syndromementioning
confidence: 66%
“…To improve the overall gastrointestinal symptoms and psychological well-being must also be taken into consideration. Treatment with PPI did not improve gastrointestinal symptoms, which further underlines the conclusion that PPI has no place in the treatment of IBS [25,26]. Irritable bowel syndrome and other functional bowel syndromes are mainly affecting younger persons [23,25], whereas our patients with MC are older.…”
Section: Patients With Irritable Bowel Syndromementioning
confidence: 66%
“…Psychological intervention can improve the general well-being and quality of life of patients with GI symptoms and also influence the outcome of medical and surgical treatment [11]. Tricyclic antidepressants and selective serotonin reuptake inhibitors have shown to improve visceral analgesic effect in esophageal pain in patients with non-cardiac chest pain [12].…”
Section: Need Of Psychological Interventionmentioning
confidence: 99%
“…Importantly, it still remains to be elucidated which factor is causative. Several studies have demonstrated that patients exposed to prolonged life stressors are more likely to complain of symptoms of GERD [14]. Vital exhaustion, a measure of sustained stress, is the most common parameter that correlates with heartburn [15].…”
mentioning
confidence: 99%